SEM2: A computational framework to model multiscale mechanics with subcellular elements - Chattaraj, Sandipan; Torre, Michele; Kalcher, Constanze; Stukowski, Alexander; Morganti, Simone; Reali, Alessandro; Pasqualini, Francesco Silvio (bioRxiv, 2023)
Modeling multiscale mechanics in shape-shifting biological tissues in embryos, traditional, or engineered cell culture platforms (organoids, organs-on-chips) is both important and challenging. In fact, it is difficult to model relevant tissue-level structural changes mediated by discrete events at the cellular and subcellular levels, such as migration and proliferation. To accomplish this, we leveraged the subcellular element modeling (SEM) method, where ensembles of coarse-grained particles interacting via empirically defined potentials are used to model individual cells while preserving cell rheology. However, an explicit treatment of multiscale mechanics in SEM was missing. Here, we introduced SEM2, an extended version of the open-source software SEM++ and LAMMPS, enabling new analyses and visualization of particle-level stress and strain. We demonstrated various functionalities of SEM2 by simulating cell creep, migration, and proliferation in scenarios that recapitulate classical and engineered cell culture platforms. For every scenario, we highlight key mechanobiology that emerges spontaneously from particle interactions and discuss recent experimental evidence as qualitative validations of our simulations. The code for SEM2 is available on GitHub at https://github.com/Synthetic-Physiology-Lab/sem2.